Pursuing Financial Stability Under an Inflation-Targeting Regime - Q. Farooq Akram; Gunnar Bardsen; Kjersti-Gro Lindquist (Norges Bank, 2006)
We evaluate two main views on pursuing financial stability within a flexible inflation-targeting regime. It appears that potential gains from an activist or precautionary approach to promoting financial stability are highly shock dependent. We find support for the conventional view that concern for financial stability generally warrants a longer target horizon for inflation. The preferred target horizon depends on the financial stability indicator and the shock. An extension of the target horizon favoring financial stability may contribute to relatively higher variation in inflation and output.
hdl:11250/2498367
Keywords: C21; C52; C53; E47; E52; 330; monetary policy; financial stability